Attitudes of polish medical students toward organ donation - Mikla, Marzena; Cybulska, Anna Maria; Rios, Antonio; Panczyk, Mariusz; Rachubińska, Kamila; Kotwas, Artur; Karakiewicz, Beata; Grochans, Elżbieta; Schneider-Matyka, Daria (Frontiers in Public Health, 2025)
BackgroundThe aim of the study was to analyze determinants affecting attitudes toward organ donation among medical students at medical universities in Poland.Materials and methodsThe study involved 1,348 medical students. It was performed using a validated questionnaire of attitude toward organ donation and transplantation (ODT) [PCID-DTO RIOS: A questionnaire designed by the International Collaborative Organ Donation project about organ transplantation and donation].ResultsIt was shown that those who would not donate their family member’s organs for transplantation were far more likely to believe it was not their moral duty (p = 0.013) and to feel no solidarity with those in need (p = 0.000). Those who spoke to their families believed it was their moral duty (p = 0.000), and believed they would do it out of solidarity with those in need (p = 0.000). It was found that having family conversations about donating one’s organs for transplantation was statistically significantly related to being a blood donor (p = 0.002), fear of desecration/disfigurement of the body after death in case of organ donation (p = 0. 000), a belief that it may be necessary to become an organ recipient in the future (p = 0.000), and knowledge of loved ones’ opinions about ODT (father p = 0.000, mother p = 0.000), partner (p = 0.000).Conclusion1. The reluctance to donate the organs of loved ones for transplantation is accompanied by a lack of a sense of moral obligation and a lack of solidarity with those in need. Conversely, conversations among loved ones about organ donation are thought-provoking, causing a sense of moral obligation and solidarity with those in need. 2. Regardless of the stance on organ donation and family discussions on the subject, the respondents do not care what happens to the body after organ donation, but they also do not know the opinions of their loved ones about ODT. 3. Conversations with loved ones contribute to the acceptance of circumstances in which organs would be harvested for transplantation without consent.